2020
DOI: 10.1093/ntr/ntaa203
|View full text |Cite
|
Sign up to set email alerts
|

Mobile, Remote, and Individual Focused: Comparing Breath Carbon Monoxide Readings and Abstinence Between Smartphone-Enabled and Stand-Alone Monitors

Abstract: Introduction Newly available, smartphone-enabled carbon monoxide (CO) monitors are lower in cost than traditional stand-alone monitors and represent a marked advancement for smoking research. New products are promising, but data are needed to compare breath CO readings between smartphone-enabled and stand-alone monitors. The purpose of this study was to: 1) determine agreement between the mobile iCO TM (Bedfont ® Scientific Ltd.) with two other monitors from the same manufacturer (Micro +TM p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…There is recent evidence that the iCO can produce a slightly higher CO reading than more conventional CO monitors [ 20 ]. However, the iCO has not been compared with other monitors during pregnancy; therefore, we retained the cut-off of < 4 ppm for the iCO during testing for eligibility.…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is recent evidence that the iCO can produce a slightly higher CO reading than more conventional CO monitors [ 20 ]. However, the iCO has not been compared with other monitors during pregnancy; therefore, we retained the cut-off of < 4 ppm for the iCO during testing for eligibility.…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…During COVID-19, for the 3- and 12-month postpartum outcomes for smoking cessation, if it is not possible to take an expired CO reading during a face-to-face visit, participants will take a CO reading using a self-administered/single-person use device (iCO TM Smokerlyzer, Bedfont Scientific Ltd.) [ 28 ] and send the CO reading to the stop smoking advisor via an app. There is recent evidence that the iCO can produce a slightly higher CO reading than more conventional CO monitors [ 20 ]. However, the authors of this study recommend an optimal cut-off for the iCO of < 6 ppm; therefore, we decided to retain our more liberal cut-off of < 8 ppm.…”
Section: Methods: Participants Interventions and Outcomesmentioning
confidence: 99%
“…During COVID-19, for the three and 12-month postpartum outcomes for smoking cessation, if it is not possible to take an expired CO reading during a face-to-face visit, participants will take a CO reading using a self-administered/single person use device ((iCO TM Smokerlyzer, Bedfont Scientific Ltd.) [27] and send the CO reading to the stop smoking advisor via an app. There is recent evidence that the iCO monitor can produce a slightly higher CO reading than more conventional CO monitors [20]. However, the authors of this study recommend an optimal cut-off for the iCO of <6ppm, therefore we decided to retain our more liberal cut-off of <8ppm.…”
Section: Assessing Smoking Cessation Outcomes During Covid-19 Restrictions On Face-to-face Contactmentioning
confidence: 97%
“…There is recent evidence that the iCO monitor can produce a slightly higher CO reading than more conventional CO monitors [20]. However, the iCO has not been compared with other monitors during pregnancy, therefore we retained the cut-off of <4ppm for the iCO during testing for eligibility.…”
Section: Participant Eligibilitymentioning
confidence: 99%
“…The latter issues are increasingly being acknowledged among researchers on professional listservs and in other professional discussion forums. The extent of problems with remote testing may well be under‐reported in the literature, although some published studies have reported substantial rates of unusable samples [5] or inconclusive results [6] as well as systematically different readings from a smartphone‐connected remote CO monitor relative to other models made by the same company [7].…”
mentioning
confidence: 99%